WRITING SCIENTIFIC ARTICLE: ISLAMIC HIGH SCHOOL TEACHERS’ PROBLEMS AND POSSIBLE SOLUTIONS - Hustarna Hustarna; Melati Melati; Radiatan Mardiah; Rachmawati Rachmawati; Susanah Susanah (Universitas Jambi, 2020)
Writing scientific article is one of the ways to develop teacher professionalism. However, writing scientific article remains a problem for some Islamic High School Teachers. To explore about the problem, a preliminary research was conducted. Focus Group Discussion was used to gather the data. The result showed that most of the Islamic High School teachers who became the participants of the research never publish a scientific article because they get difficulties not only in exploring the ideas but also in writing the article itself. The teachers admitted that writing scientifically is not their habit. Thus, encouraging those teachers to write scientifically is highly necessary and supportive atmosphere among teachers should be developed. It takes time to develop a belief that writing and publishing scientific article would help the participant teachers developing their professionalism.